Mode of perpetuation of Peronospora alta causing downy mildew of blond psyllium (Plantago ovata) - RATHORE*, B.S. (Indian Phytopathology, 2009)
Viability of conidia of the downy mildew pathogen of blond psyllium progressively reduced with the increase in storage time and temperature. While increase in RH increased the viability, an increase in storage time had the opposite effect. The survival period of conidia was found to be 9 to 11 days depending on the storage at different levels of temperature and humidity. Germination of conidia decreased with an increase in time of exposure to sunlight. It was found that oospores survived for 55.5 months under laboratory conditions when stored in the form of powdered debris. Viability of oospores was reduced when oospores were mixed with soil and with the increase in storage period. Viability of oospores decreased with increasing depth and duration of burial. Leaf debris, seeds and soil can serve as source of primary inoculum up to 43.5,55.5 and 31.5 months, respectively. The maximum disease incidence occurred when seeds from infected plant were sown 7.5 months after harvest. Further, the whole mount method revealed that 17 per cent seeds contained mycelium and 7 per cent showed presence of oospores in the internal seed tissues except embryo.